Mapping Digital Readiness To Support An Inclusive Digital Economy Using Indonesia’s Digital Society Index - Lutfi Aulia Ari Shafa (proceedings.icesy, 2026)
Digital transformation in Indonesia has become a key driver for promoting inclusive economic development by enhancing access, building digital capacities, and empowering communities within the digital economy. Despite national-level efforts, regional disparities in digital readiness remain evident, with some provinces lagging in infrastructure, digital skills, and community empowerment. This study aims to identify regional characteristics based on digital economic inclusivity using K-Means clustering applied to four main dimensions of the Indonesian Digital Society Index (IMDI): digital infrastructure and ecosystems, digital skills, community empowerment, and employment. The analysis identifies three distinct clusters of provinces: Cluster 1 with medium digital readiness, characterized by moderate infrastructure, skills, and empowerment but relatively higher employment; Cluster 2 with low digital readiness across nearly all indicators; and Cluster 3 with high digital readiness, with strong infrastructure, skills, and empowerment, although employment remains moderate. The findings reveal significant regional disparities and provide essential insights for policymakers to design targeted strategies that foster a more inclusive digital economy in Indonesia.